2012
DOI: 10.34071/jmp.2012.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Single Port Laparoscopic Cholecystectomy in Hue Central Hospital

Abstract: Purpose: Evaluating the initial results in applying single port laparoscopic cholecystectomy at Hue Central Hospital. Patients and methods: 29 gallbladder polyps, gallstones with symptoms of acute or chronic cholecystitis and surgeried by single port laparoscopic cholecystectomy at Hue Central Hospital from March 2011 to December 2011. Results: Male/female was 0.45/1. Age: 49.24 ± 16.43 (21-81), 40 to 60 years 54.6%. Cholecystitis: 75.9%, 17.3% gallbladder polyp, gallbladder adenomyomatosis 3.4%. Added 1 troca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The study assessed the effects of coffee on the brain among 17,702 UK Biobank participants aged 37-73. [11] 'Drinking coffee in moderation is associated with a lower risk of dementia, but the highest risk of dementia is associated with heavy coffee consumption,' said team member David Llewellyn, Professor of Epidemiology and Digital Health at the University of Exeter, UK. 'We found that drinking more than six cups of coffee/day was associated with 53% increase in dementia risk in comparison with people drinking one or two cups/day.…”
Section: Role Of Caffeinementioning
confidence: 99%
“…The study assessed the effects of coffee on the brain among 17,702 UK Biobank participants aged 37-73. [11] 'Drinking coffee in moderation is associated with a lower risk of dementia, but the highest risk of dementia is associated with heavy coffee consumption,' said team member David Llewellyn, Professor of Epidemiology and Digital Health at the University of Exeter, UK. 'We found that drinking more than six cups of coffee/day was associated with 53% increase in dementia risk in comparison with people drinking one or two cups/day.…”
Section: Role Of Caffeinementioning
confidence: 99%
“…Figure 1A shows the increasing trend in primary bile acids, while Figure 1B presents the declining trend in 3-oxo-D4 bile acids in three patients. Pham et al Medicine (2022) 101:25 Medicine symptoms and signs. After 6 months of treatment, all laboratory tests were within normal ranges (Table 1).…”
Section: Patientmentioning
confidence: 99%
“…This parylene layer is removed over the landing metal at bottom of the via by dry etching in an oxygen plasma. The patterning is achieved by spray coating of photoresist where a special process with heated chuck is developed for improved corner coverage [3]. The Ti/Cu seed layer is then deposited for the consecutive electroplating of 5-20µm thick Cu layer which serves as the main conductive path between the silicon wafer front and back.…”
mentioning
confidence: 99%